Criminological analysis of narcotics crime verdicts committed by members of the military (Study of Military Court Decisions) - Sri Widodo (Dynamics of Politics and Democracy, 2024)
Purpose: The main problems in this research are: (1) How is the construction of narcotics crimes committed by military personnel reviewed from legal and criminological aspects? (2) What is the background to the judges’ decisions to impose penalties for narcotics crimes?. Research/methodology: This study uses normative legal research with a descriptive-analytical approach. The data used were secondary data supported by interviews. The analysis was qualitative, and conclusions were drawn deductively. Results: Based on the results and discussion, it was concluded that the construction of narcotics crimes committed by military personnel was viewed legally from three military court decisions, each describing the reasoning behind not dismissing the offenders. Criminologically, it refers to Rational Choice Theory (RCT), where individuals freely choose to obey or violate rules based on rational considerations. This theory is supported by the legal documents and interview data. Military judges should impose stricter sanctions on such offenders to ensure a deterrent effect, educate others, and improve public perception of the Indonesian National Army. Conclusion: Weak punishment for military narcotics offenders risks reducing the authority of the military judiciary and damaging institutional reputation. Limitation: This study is limited to three court decisions and selected expert sources, which may not represent all the cases. Contribution: This study highlights the inconsistencies in sentencing military drug offenders and calls for stronger and more consistent sanctions to reinforce deterrence and restore institutional integrity.